2002
DOI: 10.1093/humrep/17.5.1292
|View full text |Cite
|
Sign up to set email alerts
|

Polyploidy in large-headed sperm: FISH study of three cases

Abstract: These observations suggested that both meiotic I and II divisions were affected by incomplete partition of homologous chromosomes during meiosis I and of sister chromatids during meiosis II associated with a failure of nuclear cleavage. Furthermore, they provide evidence for a clear relationship between a specific morphological abnormality of the sperm and their abnormal cytogenetic content. The treatment of infertility using ICSI would probably be unsuccessful and have a high genetic risk in these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
2
11

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 24 publications
1
48
2
11
Order By: Relevance
“…68,69 There are a few case reports of extraordinarily high levels of aneuploid and polyploid sperm (50-100%) in individuals with a high proportion of macrocephalic, multinucleated and multiflagellate sperm. [70][71][72][73] It perhaps counterintuitive but there is little or no evidence to suggest that there is a preferential selection of chromosomally normal sperm for fertilization. In fact, the threefold increase in aneuploidy observed in sperm from infertile men, is mirrored by a threefold increase in de novo chromosome abnormalities observed in conceptuses after intracytoplamic sperm injection compared to the general population.…”
Section: The Relationship Between Chromosome Aneuploidy and Male Infementioning
confidence: 99%
“…68,69 There are a few case reports of extraordinarily high levels of aneuploid and polyploid sperm (50-100%) in individuals with a high proportion of macrocephalic, multinucleated and multiflagellate sperm. [70][71][72][73] It perhaps counterintuitive but there is little or no evidence to suggest that there is a preferential selection of chromosomally normal sperm for fertilization. In fact, the threefold increase in aneuploidy observed in sperm from infertile men, is mirrored by a threefold increase in de novo chromosome abnormalities observed in conceptuses after intracytoplamic sperm injection compared to the general population.…”
Section: The Relationship Between Chromosome Aneuploidy and Male Infementioning
confidence: 99%
“…In case of fetuses conceived after ICSI, increased aneuploidy rate has been reported [17], which particularly concerned gonosomes [18], probably due to increased sperm aneuploidy rate in infertile patients [19][20][21]. Spermatozoa morphological abnormalities, including macrocephalia [22,23], asthenospermia [24] and globozoospermia [25,26] are known to be associated with increased aneuploidy rate. These abnormalities are regarded as a justification for preimplantation genetic screening in some countries [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…19,20 It is in fact a meiotic non-disjunction with no cell division and spermiogenesis. In a study on ten patients with polyploid macrocephalic spermatozoa, Dieterich demonstrated a mutation of the Aurora Kinase C gene (AURKC) in a molecular analysis.…”
Section: Pathogenesismentioning
confidence: 99%